2015
DOI: 10.1021/acs.jafc.5b02127
|View full text |Cite
|
Sign up to set email alerts
|

H, C, and O Stable Isotope Ratios of Passito Wine

Abstract: In this study we investigated the effect of the grape withering process occurring during the production of Italian passito wines on the variability of the (D/H)I, (D/H)II, δ(13)C, and δ(18)O of wine ethanol and the δ(18)O of wine water. The production of PDO Erbaluce di Caluso Passito in five different cellars in Piedmont (Italy) was considered in two successive years. Moreover, samples of 17 different traditional Italian passito wines taken at different stages of maturation were taken into account. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Studies have demonstrated that the 18 O/ 16 O ratio is a useful footprint for wine origin (Perini et al ., 2015; Orellana et al ., 2019; Bononi et al ., 2020) because oxygen is actively involved in the metabolism of the plants and undergoes little fractionation during the process of the plant growth. The climate and location have the strongest relationship with δ 18 O, as oxygen isotope value was positively correlated with oxygen isotope value of water and negatively correlated with precipitation (Camin et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have demonstrated that the 18 O/ 16 O ratio is a useful footprint for wine origin (Perini et al ., 2015; Orellana et al ., 2019; Bononi et al ., 2020) because oxygen is actively involved in the metabolism of the plants and undergoes little fractionation during the process of the plant growth. The climate and location have the strongest relationship with δ 18 O, as oxygen isotope value was positively correlated with oxygen isotope value of water and negatively correlated with precipitation (Camin et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…These differences can be explained by the average precipitation during the harvest and the altitude of each individual region. There was no difference in oxygen isotope between Italian wine and grape juice, ranging from −2‰ to −6‰ (Perini et al ., 2015). δ 18 O in Washington and California ranges from −3‰ to 5‰ and 2‰ to 14‰ (Orellana et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 This investigation was based on flour samples grown with synthetic nitrogen fertilizer animal manure and green manure from atmospheric nitrogen fixing legumes, and the results demonstrate that the molecular amino acid δ 15 N isotope profile is different in samples, depending on the relative source of nitrogen. Perini et al 3 report the use of stable isotope ratio analysis to verify the authenticity of Passito wine. The effect of the grape's withering process on the variability of the (D/H) I , (D/H) II , and δ 13 C of wine ethanol and the δ 18 O of wine water were monitored.…”
Section: ■ Food Authentication and Traceabilitymentioning
confidence: 99%